The Myth and Mystery of UFOs - Bullard, Thomas E. (Thomas Eddie), 1949- (Book collections on Project MUSE., 2010)
Bullard shows how ongoing grassroots interest in UFOs stems both from actual personal experiences and from a cultural mythology and also how UFOs have catalyzed the evolution of a new but highly fractured belief system that borrows heavily from the human past and mythic themes.